MODEL PEMANFAATAN LAHAN PULAU MOTI, KOTA TERNATE, MALUKU: SUATU ANALISIS TATA RUANG BERBASIS VEGETASI - Roemantyo, Roemantyo (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTLand Use Model of Moti Island, Ternate, Moluccas: A Vegetation Based Spatial Design Analysis.The Moti Island was dominated by mountain areas and humitropepts soil type which havehigh organic matter and low subsoil base saturated values. Geologically, it is a volcanic rockwith andesite composition includes lava, breccias and tuffs volcanic. Combined with highrainfall, width of island (24.6 km2) and very steep mountain (950 m asl.) the island has becomefragile when not well managed. Compared to the other district, the productivity of this area waslow because the natural resources have not been well developed yet. The shortage ofbiodiversity data of Moti Island has become major obstacles in developing Moti Island. Thisresearch was conducted to develop land use models as basic knowledge for spatial designanalyses of Moti Island. Detail discussion on developing Digital Elevation Model of land useand slope area based on vegetation data was presented in this paper.Key words: Moti, land use, digital elevation model (DEM), spatial designing analyses